EVOLUTION OF THE COSTUME ARTISTIC AND FIGURATIVE PRESENTATION BY CLOTHING DEMONSTRATION (BASED ON THE UKRAINIAN PERIODICALS MATERIALS OF THE 1930s–1990s) - Дихнич , Л. П. (Art and Design, 2023)
Purpose is to highlight the main stages and characteristic features of the costume artistic presentation in the context of the clothing demonstrator profession formation based on the periodicals materials in the territory of Ukraine in the 1930s–1990s. Methodology of the research has been based on the historical, visual-analytical methods and the method of artistic-compositional analysis of photos and clothing models. Results. Samples of fashionable costumes of the 1930s-1990s period, represented with the help of clothing demonstrators on the pages of such periodicals for women as "Nova Khata" ("New House"), "Radianska zhinka" ("Soviet Woman"), as well as such specialized fashion publications as "Krasa i Moda" ("Beauty and Fashion"), "Za narodnymy motyvamy" ("Based on Folk Motifs"), "Novi modeli" ("New models") have been examined in the study. Photo-artifacts have been analyzed in the context of historical realities and considering the peculiarities of the clothing demonstrator phenomenon formation as an independent profession within the Ukrainian fashion industry. Scientific novelty. For the first time, the study reveals the gradual transition from advertising photos with female images without names to the establishment of an independent type of professional activity of models - fashion demonstrators; reveals the stages and characteristic features of the artistic and figurative presentation of the costume, due to the formation and development of the profession of a fashion demonstrator in the context of the development of Ukrainian fashion in the 1930s–1990s. Photographic materials from periodicals of the period are introduced into scientific circulation. Practical significance. Photo-materials of the Ukrainian periodicals of the 1930s–1990s, which have been collected and systematized for decades, have enabled to trace the clothing demonstrator profession origin and development, as well as the nature of the clothing designers ideological communication with the consumer audience in the Soviet period. The results of the study can be used in teaching practice of the Design and Fashion History disciplines, as well as in further research of the fashionable clothes representation with the participation of fashion demonstrators in Ukraine.